Large signal and noise properties of heterojunction AlxGa1−xAs/GaAs DDR IMPATTs. (June 2016) - Banerjee, Suranjana; Mitra, Monojit
Abstract: Simulation studies are carried out on the large signal and noise properties of heterojunction (HT) Al x Ga1− x As/GaAs double drift region (DDR) IMPATT devices at V-band (60 GHz). The dependence of Al mole fraction on the aforementioned properties of the device has been investigated. A full simulation software package has been indigenously developed for this purpose. The large signal simulation is based on a non-sinusoidal voltage excitation model. Three mole fractions of Al and two complementary HT DDR structures for each mole fraction i.e., six DDR structures are considered in this study. The purpose is to discover the most suitable structure and corresponding mole fraction at which high power, high efficiency and low noise are obtained from the device. The noise spectral density and noise measure of all six HT DDR structures are obtained from a noise model and simulation method. Similar studies are carried out on homojunction (HM) DDR GaAs IMPATTs at 60 GHz to compare their RF properties with those of HT DDR devices. The results show that the HT DDR device based on N-Al x Ga1− x As/p-GaAs with 30% mole fraction of Al is the best one so far as large signal power output, DC to RF conversion efficiency and noise level are concerned.